A Comparative Study of Euthyroid and Primary Hypothyroid Patients in End Stage Renal Disease (ESRD) Undergoing Maintenance Hemodialysis (MHD) in a Tertiary Care Hospital in Salem, Tamil Nadu - Chinnathambipalayam Kandasamy Vijayasamundeeswari; Byna Jayachandrababu; Sandip Kumar Kundu; Kamala Kanta Parhi; P. Jones Ronald; Panneerselvam Periasamy (Journal of Pharmacy and Bioallied Sciences)
Background and Aim: Hypothyroidism significantly alters renal function. Still, there are few scientific studies on thyroid disorders and how it influences renal function. Recent research suggested hypothyroidism may lower the glomerular filtration rate. This study aimed to assess changes in renal function biochemical parameters in MHD patients with primary hypothyroidism. Methods: 132 patients with MHD participated in a prospective research who had untreated primary hypothyroidism and euthyroidism. Immunoassay was used to quantify thyroid-stimulating hormone (TSH), free thyroxine (fT4), and free triiodothyronine (fT3). Renal parameters; urea and creatinine were measured in fully automated biochemical analyzer and estimated glomerular filtration rate (eGFR) was calculated by the Modification of Diet in Renal Disease (MDRD) formula. Results: In comparison with euthyroid MHD patients with primary hypothyroid MHD patients have higher significant values of TSH, creatinine, SBP, DBP as 3.57 ± 1.15 vs 10.49 ± 6.40, 8.23 ± 2.40 vs 9.31 ± 2.49, 155.87 ± 5.84 vs 162 ± 6.82, 91.73 ± 6.14 vs 98.64 ± 6.28. The fT4, fT3 and eGFR value reduced significantly in primary hypothyroid MHD patients as compared to euthyroid MHD patients as 1.10 ± 0.24 to 0.44 ± 0.21, 2.65 ± 0.89 to 1.13 ± 0.24 and 6.82 ± 2.5 to 5.40 ± 1.66, respectively. Discussion: Our study demonstrated that in primary hypothyroid patients due to increase of SBP and DBP glomerular feedback is increased as a result creatinine excretion decreased. So GFR decreased leads to decreased iodine clearance and can cause decreased synthesis of thyroid hormones leading to primary hypothyroidism in MHD patients. Conclusions: Thyroid dysfunction is linked to impaired kidney function, making it crucial for clinicians to understand this connection in patients with multiple myeloma (MHD), and monitoring creatinine is essential.